PROGRAM OF LABOR GYMNASTICS IN UNIVERSITY RESTAURANT - GARCIA, DÉBORA RIOS (Fiep Bulletin - online, 2015)
Introduction: The life of the modern man is each time more directed to the confrontation of situations criticizes for its subsistência such as feeding, housing, transport, education, health and the proper maintenance of the job, all they, generating situations of stress. The administration of this stress if has shown to a vital tool in the tests techniques of enterprise administration showing, comprovadamente, that she has improvement in the levels of quality of life. Therefore, the gymnastics in the workstation acts of preventive and therapeutical form. Objective: the elaboration of this research had as objective to investigate the reasons and feelings that had taken the employees of the restaurant of a University of Are Leopoldo to carry through the program of Labor Gymnastics. Methodology: The sessions of Labor Gymnastics had been carried through daily, two times per day 15 minutes. The sessions had congregated exercises, allonges, muscular relaxation and mobility respiratory to articulate aiming at the reduction of stress, improvement of the quality of life of the employee. The sample was composed for 31 women who work regularly in the restaurant. The participants had been in accordance with resolution 196/96 of the National Advice of Health. Results: The gotten results suggest that 37% of the employees feel when carrying through the gymnastics more relaxed; 33,3% had observed that they had diminished the esqueléticas injuries muscles; 22,2% had told that the gymnastics prevented pains to them; 14,8% are felt awaken and warm for the professional activity that they play; 14,8% feel relief of stress and 11.1% had pointed improvement in the health. 27% of the interviewed ones had pointed that the program assisted in the relaxation of the body; 53% had felt the light and prolongated body; finally, 100% of the employees they approve the program of Labor Gymnastics. Conclusion: We can conclude that the program of Labor Gymnastics reached its ojetivos. The participants had demonstrated the results, as, for example, that they had felt themselves relaxed and that the reasons to make the Gymnastics were well diverse, but all directed the improvement of the welfare. All, had affirmed that the participation in the Program of Labor Gymnastics brought greater satisfaction in the accomplishment of its daily tasks.